Innovative outcome through exploration and exploitation – Enablers, barriers and industrial property. Issue 1 (19th July 2021) - Vargas, Nancy; Lloria, M. Begoña; Salazar, Addisson; Vergara, Luis
Abstract : Purpose: This research aims to study the effect of R&D (research and development) enablers and barriers as well as industrial property on exploration, their influence on exploitation and finally the possible impact on innovative outcome (IO) as a result variable. The IO can be defined as the orientation towards new or improved products, services and processes, as well as towards penetration and greater market share, which the company has obtained as a result of innovative processes. Design/methodology/approach: For this purpose, a new relationship model is defined, which is empirically contrasted in a quantitative study. We use a sample of large firms from different economic sectors with a high level of investment in R&D. Findings: The results indicate a close relationship between exploration and exploitation processes, as well as a positive impact on the innovative outcome. Moreover, the type of relationship that R&D enablers and barriers have with exploration is demonstrated and the lack of a positive effect of industrial property on exploration. Practical implications: These results may lead to new markets opening up and the creation or improvement of new products, services or processes in diverse sectors of highly innovative firms. Originality/value: This research aims to study the effect of R&D enablers and barriers and industrial property on learning flows and, finally, the possible impact on the innovative outcome. A new theoretical model of relationships is defined, and it is the first time that it is empirically tested. 研究目的: 本研究旨在探討研究與開發的推動者、研發的障礙和工業產權對探索與開發的影響，並最終探究出其可能對作為結果變項的創新成果帶來的影響。創新成果可解釋為邁向新的或改良的產品，服務和流程的定向，以及邁向滲透和更大的市場份額的定向，而這更大的市場份額是企業的創新流程所帶來的。 研究的設計/方法/理念: 為達研究目的，我們解說了一個新的關聯模型, 並使用於一項量化研究，進行以實驗為依據的對比。我們使用的樣本，包括來自不同經濟領域，並於研發投放高水平投資的大企業。 研究結果: 研究結果顯示，探索與開發是兩個關係密切的流程；研究結果亦顯示對創新成果的影響是正面的。而且，結果展示了研發推動者、研發障礙兩者與探索的關聯，以及工業產權對探索是欠缺正面作用的。 實際的意義: 研究結果或會帶來新市場的開拓，以及在不同領域、高度創新的企業內，帶來新的產品，服務與流程的創造和改良。 研究的原創性和價值: 本研究旨在探討研發推動者，研發障礙和工業產權對學習心流的影響，並最終探究出其對創新成果可能帶來的影響。研究解說了一個新的、純理論的關聯模型，而這個模型於此是首次憑實驗而被測試的。